1998
DOI: 10.1177/014107689809100502
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress and burnout in medical students: a five-year prospective longitudinal study

Abstract: SUMMARYThe aim of this study was to assess psychological morbidity and symptoms of bumout in medical students during their undergraduate training, and to identify baseline factors that predict psychological morbidity in students in the final year of the course. It was a 5-year prospective longitudinal cohort study. Students were assessed in years 1, 4 and 5 of their medical undergraduate training by means of the GHQ-12 and the Maslach Burnout Inventory.172 (84.3%), 157 (77.0%) and 155 (75.9%) students out of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
269
12
30

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(345 citation statements)
references
References 11 publications
34
269
12
30
Order By: Relevance
“…It has been observed that medical students have marked undue stresses during pre and examination period 23 . The results are well in agreement with the previous studies were students experience stress during the first year but not in subsequent years 24,25,26 . The medical students are always vulnerable to stress due to their high competitive environment.…”
Section: Discussionsupporting
confidence: 93%
“…It has been observed that medical students have marked undue stresses during pre and examination period 23 . The results are well in agreement with the previous studies were students experience stress during the first year but not in subsequent years 24,25,26 . The medical students are always vulnerable to stress due to their high competitive environment.…”
Section: Discussionsupporting
confidence: 93%
“…5,7,12,[17][18][19] The different sources of stress to which medical students are exposed during their medical training are well known. 18,26,27 Medical education is hard to access and difficult to sustain, given the large amount of time dedicated to academic activities and the amount of suffering and distress that students need to cope with on a daily basis. Overwhelming activities, along with contact with disease and death early in life, are among the factors that explain the high prevalence of depression and burn-out and the perception of poor quality of life that are commonly reported in medical student surveys.…”
Section: Consequences Of Mistreatment On the Way Students Perceive Mementioning
confidence: 99%
“…intake [14][15][16]. The study developed by Moffat, McConnachie, Ross and Morrison showed that students tended to use more active coping strategies (e.g.…”
Section: Journal Of Community Medicine and Health Educationmentioning
confidence: 99%
“…On the other hand, with the new learning curriculum, the group learning environment, the tutor's performance and interactions with peers and patients caused little stress [17]. However, these results are controversial, as in another research problems with tutors were identified as stressors [15].…”
Section: Problem Based Learning (Pbl)mentioning
confidence: 99%